Considerations for Embedding Inclusive Research Principles in the Design and Execution of Clinical Trials - Peters, Ubong; Turner, Brenna; Alvarez, Daniel; Murray, Makaelah; Sharma, Aruna; Mohan, Shalini; Patel, Shilpen (Therapeutic innovation & regulatory science, 2023)
There is a growing recognition that the clinical research enterprise has a diversity problem, given that many clinical trials recruit historically marginalized individuals or patients reflective of real-world data at a rate that is far below the incidence and prevalence of the disease for which the investigational therapy or device is targeting. This lack of diversity in clinical research participation can obscure the safety and efficacy of drug therapies and limits our collective ability to develop effective treatments for all patients, leading to even wider health disparities. This review article provides an in-depth analysis of the impact of this bias on public health, along with a description of some of the barriers that prevent historically marginalized populations from participating in clinical research. Some practical solutions that can be employed to increase diversity in clinical trial participation are also discussed, including the crucial role clinical trial sponsors, research organizations, patients, and caregivers need to play in supporting the industry to achieve this ambitious but necessary goal.